Enhancing Literacy and Numeracy through Inquiry-Based Learning: The Impact of E-Lens as an Innovative Board Game - Subekti, Puji; Rahayu, Widya Adhariyanty (Universitas Pendidikan Ganesha, 2024)
The problem faced is the low literacy and numeracy skills of students, which pose a challenge for conventional teaching methods. This study aims to analyze the effectiveness of the inquiry-based learning game, E-Lens, in improving students' literacy and numeracy. The study employs a quasi-experimental design with pre-test and post-test methods, involving two groups: the experimental group using E-Lens and the control group using conventional teaching methods. The instruments used include literacy and numeracy tests, questionnaires, and classroom observations. Data were analyzed using statistical analysis, including ANCOVA, to compare the results between the two groups. The findings show that the use of E-Lens significantly improves students' literacy and numeracy compared to the control group. Statistical analysis also reveals a strong negative correlation between pre-test scores and post-test improvements, with students who initially scored lower showing greater gains. Teacher evaluations indicate that E-Lens is easy to implement and enhances student engagement. The conclusion of this study is that E-Lens has been proven effective in improving students' literacy and numeracy and can serve as an innovative solution to enhance the quality of education in Indonesia.